Approaches to manipulating microRNAs in neurogenesis - Zhang, Haijun; Shykind, Benjamin; Sun, Tao (Frontiers in Neuroscience, 2013)
Neurogenesis in the nervous system is regulated by both protein coding genes and noncoding RNA molecules. microRNAs (miRNAs) are endogenous small noncoding RNAs and usually negatively regulate gene expression by binding to the 3’ untranslated region (3’UTR) of target messenger RNAs (mRNAs). miRNAs have been shown to play an essential role in neurogenesis, regulating neuronal proliferation, differentiation, maturation and migration. An important strategy used to reveal miRNA function is the manipulation of their expression levels and patterns in specific regions and cell types in the nervous system. In this review we will systemically highlight established and new approaches used to achieve gain-of-function and loss-of-function of miRNAs in vitro and in vivo, and will also summarize miRNA delivery techniques. As the development of these leading edge techniques come online, more exciting discoveries of the roles miRNAs play in neural development and function will be uncovered.